Segmentation of the electric scooter market in Poland - Kubiczek, Jakub; Hadasik, Bartłomiej (Segmentacja rynku hulajnóg elektrycznych w Polsce, 2020)
The growing popularity of electric scooters has resulted in the dynamic development of this market on a global scale. Each potential customer has different preferences and therefore should be able to choose a scooter that meets their expectations. The study used a dataset comprising 42 scooters available on Polish market with their specifications. The aim of the study was to present the structure of the electric scooter market in Poland and carry out a market segmentation. On the basis of an arbitrary decision, under the terms of the quotients of the coefficients in successive stages of combining into clusters, two and four classes of scooters were distinguished. The comparison of clusters with the adopted price ranges proved that, with the increase in the performance of the electric scooter, the price rises. Such a combination can help customers choose the cheapest scooter from a given market segment, according to their budget constraints and personal preferences
Econometrics = Ekonometria, 2020, Vol. 24, No. 4, s. 50-65
Keywords: market segmentation; electric scooters; Poland; classification; factor analysis; segmentacja rynku; hulajnogi elektryczne; Polska; klasyfikacja; analiza czynnikowa